The accuracy of micro-core compressive test to predict the strength of concrete - Hassan, Hishamudin (2012)
In-situ compressive strength of concrete is the process of quality control of concrete. The methods widely accepted for determining the compressive strength of concrete in existing structures is concrete core test. In this study, the idea is replacing the standard core with micro-core in concrete core test. The objective of this study is to compare the compressive strength for both standard core and micro-core. According to international standards and recommendations, the most suitable diameter for testing in laboratory is 100 mm diameter. However, drilling core concrete sample on such rather large size cores may cause hazardous in many cases. In this regard, the estimate strength of concrete in structures may be gained from compression test of core having the diameter less than 100 mm. As it is not always safe to drill cores of 100 mm diameter, utilizing smaller diameters is more practical. Micro-cores have many advantages such as can be drilled in-situ with very light equipment that can greatly reduced costs and less damage to the structure. This paper examines the results of the in-situ compressive strength tests applied on 100 mm and 25 mm diameter drilled from slab specimen. The results were analyzed using linear regression analysis and detailed statistical analysis.